Guava Fruit Fly, Bactrocera correcta (Bezzi) (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr.; Thomas R. Fasulo (EDIS)
This document is EENY-200 (originally published as DPI Entomology Circular No. 291), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2001. Revised: May 2001, October 2002.